Equitable teaching for cultural and linguistic diversity: exploring the possibilities for engaged pedagogy in post-COVID-19 higher education. Issue 3 (16th April 2022) - Baker, Sally; Anderson, Joel; Burke, Rachel; De Fazio, Teresa; Due, Clemence; Hartley, Lisa; Molla, Tebeje; Morison, Carolina; Mude, William; Naidoo, Loshini; Sidhu, Ravinder
ABSTRACT: While the impacts of COVID-19 on higher education are still unfolding, it is clear that the disruption caused by the pandemic has provided a warrant to re-consider existing teaching and learning practices. We provide a reading on whether existing teaching and learning practices should be retained or whether new practices can and should emerge through the lens of culturally and linguistically diverse migrant and refugee (CALDMR) students. These students already experienced significant educational disadvantage before the pandemic moved teaching and learning online. Drawing on findings from an Australian study that explores the experiences of both university students and staff, we question whether these experiences offer hope for what bell hooks calls engaged pedagogy – as a form of university teaching and learning that is more caring, more student-centred and collaborative, and more exciting.